A automedicação em usuários da atenção primária do Sistema Único de Saúde - Flávia Helena Castro Alves (2017)
Introduction: Self-medication is a common practice defined as the selection and use of medications to treat self-diagnosed illness or symptoms, with various individual and societal benefits. Responsible self-medication is limited to the use of medicines that does not require prescriptions, called over-the-counter (OTC), which can be used safely. However, the population has used not only OTC for self-medication, but also medicines that require prescription without the necessary supervision. Self-medication when improperly exercised can put health at risk. Therefore, it is necessary to carry out specific studies in the various health care sectors, including within the scope of Primary Health Care (PHC) of the Unified Health System (SUS), to evaluate the self-medication practiced. Objectives: To analyze the reported self-medication in primary care users of the SUS, investigating the prevalence and factors associated with this practice. Describe the medications used by self-medication and know the profile of users who did not practice responsible self-medication. Methods: This is a population-based cross-sectional study using data from the National Survey on Access, Use and Promotion of the Rational Use of Medications (PNAUM) - services component, related to interviews with PHC users between July and December 2014. Those who reported using at least one medication not recommended by a physician or dental surgeon were considered selfmedication practitioners. The explanatory variables investigated were: sociodemographic, use of health services, life habits and health in general. The associated factors were evaluated by multiple logistic regression and the results presented by odds ratio with 95% confidence intervals. The drugs consumed by self-medication were identified and classified according to the legal category. Those who reported the use by self-medication of some drug that requires prescription were considered as non-practitioners of responsible self-medication. Results: The prevalence of self-medication was 10.5% (95% CI: 8.6 to 12.9). In the multiple logistic model, the factors associated with more chance of self-medication were: being under 59 years, residing in the North, practicing physical exercises, consuming alcoholic beverages once or more per month, having no chronic disease, feeling pain or discomfort, attending the SUS rarely/never and not needing emergency care. As for drugs, analgesics and muscle relaxants were the most common therapeutic subgroups and sodium dipyrone, combinations with orphenadrine and paracetamol, the most used chemical substances. The dominant legal category was OTC medicines (66.7%). Of the interviewees, 35.9% did not practice responsible self-medication, and the most common characteristics identified in this group were: female, 30 to 59 years, married or in stable union, non-white color, incomplete elementary school education, economic class C and absence of chronic disease. Conclusion: Self-medication presented low prevalence and most of used drugs do not require prescription. However, a considerable portion of interviewed did not practice responsible self-medication. The results of this study may provide relevant subsidies to the authorities, since interventions are needed to ensure the quality of drug use and the safety of users.